A Mobile Application to Support Exclusive Breastfeeding in Vietnam: A Randomised Controlled Trial - Doan, Thi Thuy Duong (Curtin University, 2022)
Breastfeeding is important for health. A mobile application was developed to support breastfeeding for mothers in Vietnam where smartphones are widespread. The app was evaluated through a two-arm triple-blinded randomized controlled trial. Among mothers who had a caseation section, early initiation of breastfeeding and exclusive breastfeeding before discharge were significantly higher in the intervention group compared to the control one. The low-cost and widely accessible mobile application should be a component of the intervention package to improve breastfeeding.